(untitled) (Jurnal Pendidikan dan Bahasa Sastra Harapanan, 2025)
This research presents an in-depth juridical study of the legal considerations of the Constitutional Court in Decision Number 63/PUU-XIV/2016, which rejected the petition for the material judicial review of Law Number 11 of 2016 concerning Tax Amnesty. The Tax Amnesty Law is a controversial fiscal policy breakthrough , driven by the country’s urgent need to increase tax revenue, encourage the repatriation of Indonesian citizens’ assets abroad, and expand the tax database. However, its presence triggered a wide public debate and lawsuits to the Constitutional Court by various elements of civil society, including labor unions, who argued that the law violated the sense of justice, provided discriminatory treatment, and contravened the principle of the rule of law and the compulsory nature of taxation as mandated by the Constitution of the Republic of Indonesia of 1945. This study uses a normative legal research method with a statutory approach, case approach, and conceptual approach. The data used is secondary data consisting of primary legal materials in the form of the 1945 Constitution, the Tax Amnesty Law, and the Constitutional Court Decision Number 63/PUU-XIV/2016, as well as secondary legal materials in the form of trial transcripts, doctrines, and legal scholarly works. Analysis is carried out qualitatively to interpret and evaluate the arguments of the parties and the Court’s legal considerations. The discussion results indicate that the Constitutional Court in its considerations emphasized the aspect of utility (utilitarianism) and the state’s grand objective (staatsdoel) for the prosperity of the people. The Court viewed the tax amnesty policy as an open legal policy or the authority of the law-maker to address urgent economic problems, and not a form of betrayal of the constitution. The Court held that the a quo law was not discriminatory because it provided equal opportunity for all Taxpayers to participate and did not contradict the principle of compulsory taxation because its essence is the provision of a legal facility. Nevertheless, the decision is not free from criticism, especially regarding the potential erosion of justice for compliant Taxpayers and the challenges in ensuring post-amnesty compliance sustainability. This research concludes that Constitutional Court Decision Number 63/PUU-XIV/2016 is a product of pragmatic-realistic legal considerations in responding to conditions of economic urgency, but it leaves an important note regarding the balance between legal certainty, justice, and utility in fiscal policy. It is suggested that the government and the House of Representatives in the future should be more cautious in formulating policies that potentially harm the public sense of justice and that there is a need to consistently strengthen tax law enforcement post-amnesty to maintain public trust.